A redox‐active HybG‐HypD scaffold complex is required for optimal ATPase activity during [NiFe]‐hydrogenase maturation in Escherichia coli. Issue 2 (20th January 2023) - Haase, Alexander; Sawers, R. Gary
Abstract : Four Hyp proteins build a scaffold complex upon which the Fe(CN)2 CO group of the [NiFe]‐cofactor of hydrogenases (Hyd) is made. Two of these Hyp proteins, the redox‐active, [4Fe‐4S]‐containing HypD protein and the HypC chaperone, form the basis of this scaffold complex. Two different scaffold complexes exist in Escherichia coli, HypCD, and the paralogous HybG‐HypD complex, both of which exhibit ATPase activity. Apart from a Rossmann fold, there is no obvious ATP‐binding site in HypD. The aim of this study, therefore, was to identify amino acid motifs in HypD that are required for the ATPase activity of the HybG‐HypD scaffold complex. Amino acid‐exchange variants in three conserved motifs within HypD were generated. Variants in which individual cysteine residues coordinating the iron–sulfur ([4Fe‐4S]) cluster were exchanged abolished Hyd enzyme activity and reduced ATPase activity but also destabilized the complex. Two conserved cysteine residues, C69 and C72, form part of HypD's Rossmann fold and play a role in HypD's thiol‐disulfide exchange activity. Substitution of these two residues individually with alanine also abolished hydrogenase activity and strongly reduced ATPase activity, particularly the C72A exchange. Residues in a further conserved GFETT motif were exchanged, but neither hydrogenase enzyme activity nor ATPase activity of the isolated HybG‐HypD complexes was significantly affected. Together, our findings identify a strong correlation between the redox activity of HypD, ATPase activity, and the ability of the complex to mature Hyd enzymes. These results further highlight the important role of thiol residues in the HybG‐HypD scaffold complex during [NiFe]‐cofactor biosynthesis. Abstract : We delineate amino acid motifs required for optimal ATPase activity of the HybG‐HypD scaffold complex, which is required for Fe(CN)2 CO group synthesis during hydrogenase [NiFe]‐cofactor assembly. Substitution of cysteine residues coordinating the 4Fe‐4S cluster or the thiol‐disulfide exchange motif reveals that the intact redox pathway is necessary for optimal ATP‐hydrolyzing activity and functionality of the HybG‐HypD scaffold complex.